Analysis of the Implementation of Spiritual Aspects during Pregnancy and Childbirth among Pregnant Women in Bandung, Indonesia - Trisiani, Desi; Melan Meilani; Shafira Suryadinda; Yanti Herawati; Teni Nurlatifah (Arkus, 2024)
Pregnancy and childbirth are important periods in a woman's life. This period can give rise to various emotions, such as happiness, anxiety, and fear. Spiritual aspects can play an important role in helping pregnant women face this period more positively and calmly. This study aims to analyze the implementation of spiritual aspects during pregnancy and childbirth among pregnant women in Bandung, Indonesia. Data was collected through a survey of 100 pregnant women in Bandung. The results showed that the majority of pregnant women (85%) had strong spiritual beliefs and they implemented various spiritual practices during pregnancy and childbirth. The most common spiritual practices are prayer (95%), reading scriptures (70%), and meditation (55%). Pregnant women experience spiritual benefits during pregnancy and childbirth, such as inner calm (80%), mental strength (75%), and self-confidence (70%). This research shows that spiritual aspects play an important role in helping pregnant women face pregnancy and childbirth more positively and calmly.